Nora Unchained and "Margo Rising": Evil Twins at the Limits of Genre in Francine Pascal's Young Adult Franchise. Issue 2 (July 2017) - Swanstrom, Lisa
Abstract : From 1983 to 2003 Francine Pascal's hugely successful book seriesSweet Valley High dominated the young adult publishing market. For the first decade of its life, Sweet Valley 's narrative form was as conventional as the politics it portrayed, but in 1993, with the publication of its one hundredth book, something changed. In this peculiar novel, SVH #100, The Evil Twin, as well as its 1995 sequel, SVH Magna Edition #6, Return of the Evil Twin, the franchise veered from its generic conventions and tried something new—or, more accurately, tried something equally clichéd and formulaic but imported from a different genre, i.e., horror. This essay argues that the shift from romance to horror illuminates the troubling cultural and political assumptions that underpin the teenage romance and, as a consequence, threatens—and briefly manages—to subvert them.